Teacher - Parent Partnerships: Preservice Teacher Competences and Attitudes during Teacher Training in the Netherlands - Denessen, Eddie; Bakker, Joep; Kloppenburg, Lenny; Kerkhof, Marleen (International Journal about Parents in Education, 2023)
Teachers are expected to build strong relationships with their students’ parents, but little is known about the way they develop their perspectives on parent involvement and their competences in relating to parents. To gain insight in these developments, a survey study was conducted about the content of the curricula of three teacher training institutes in the Netherlands and the impact of teacher training on preservice teachers’ attitudes and competences. Surveys were administered to a total of 545 preservice teachers from all grades of their training. Overall, it seemed that levels of competence of Dutch student teachers were quite low, despite the fact that teacher training programmes provided many curricular components on this issue. Some positive though small effects of teacher training programmes have been observed. In general, however, students don’t feel well prepared to communicate with parents when starting their teaching career. Although some differences between teacher training institutes exist, the effectiveness of teacher training programmes did not appear to differ across institutes. Student teachers’ attitudes towards parents were nevertheless very positive. These attitudes, however, were not related to their teacher training experiences, but seemed to be founded in their personal biography.